Physical and structural properties of nickel zinc ferrite Ni 1-x Zn x Fe 2O 4 (x = 0, 0.2, 0.4, 0.6, 0.8, 1.0) - Siti Zuhairah, Zahari (2016)
Solid state or conventional technique is one of favorite or famous technique that used to prepared ferrite by the researchers a few decades ago. In this study, the variation of composition in preparation of Ni-Zn ferrites. The composition series Ni (1-x)Zn (x)Fe 2O 4 where (x= 0.0, 0.2, 0.4, 0.6, 0.8 and 1.0) of ferrites have been prepared using this method. The samples were prepared by double sintering. The structural, or crystallization and physical properties were studied by X-ray diffraction; Scanning electron microscope and Fourier transform infrared spectrometry. The pattern of XRD revealed a single phase cubic spinel structure for the all composition ferrites samples. The crystalline size showed the increased and decreased result which are x=0.0 to x=0.4 increased but for x=0.6 it show decreased and increased for the last two samples x=0.8 and x=1.0. The lattice parameter or constant was also investigated and from this studies, it is observed that the lattice parameter majority increased with increased the zinc content.